2021
DOI: 10.1080/13880209.2021.1969414
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect and metabonomics studies of radix gentianae in rats with acute liver injury

Abstract: Context As a well-known traditional Chinese medicine for protecting the liver, the mechanism of Radix Gentianae (RG) remains unclear. Objective The hepatoprotective effect and metabonomics of RG were studied to explore the molecular and metabolic mechanisms of RG protecting the liver. Materials and methods Sprague-Dawley rats were divided into control and model group ( n = 10, orally given distilled water), interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…50 The change of linoleic acid might indicate the hepatotoxicity is related to oxidative stress or lipolysis. 51 After 10 days of administration, linoleic acid changed significantly in GS-treated groups, but not after 21 days. Butanoic acid is a fatty acid and exists as an ester in animal, which produces ATP through mitochondria.…”
Section: Discussionmentioning
confidence: 90%
“…50 The change of linoleic acid might indicate the hepatotoxicity is related to oxidative stress or lipolysis. 51 After 10 days of administration, linoleic acid changed significantly in GS-treated groups, but not after 21 days. Butanoic acid is a fatty acid and exists as an ester in animal, which produces ATP through mitochondria.…”
Section: Discussionmentioning
confidence: 90%
“…In order to address the biological verification needs, the hepatoprotective effects of ROF on ETH-induced liver damage were assessed both in vitro and in vivo . Bifendatatum was treated as a positive control for assessing ROF in vivo , as it has previously been proven to be an anti-hepatitis drug via its mechanisms of reducing alanine transaminase secretion ( Deng et al, 2020 ; Xu S. et al, 2021 ). Bifendatatum has been used as a positive control in many alcoholic liver injury animal studies ( Wang et al, 2012 ; Bian et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study firstly showed that this soy-derived Chinese medicine could relieve the liver swelling, improve the liver function, and alleviate liver histopathology in the CCl 4challenged mice, supporting the potential of SSG as well as its EAE and NBE as protective agents against liver disorders. From the unique perspective of TCM, SSG has the effects of clearing "heat", removing "dampness", and relieving "toxin", which could explain its effectiveness in the CCl 4 -induced hepatic damage representing "dampness-heat" syndrome in TCM (Xie et al, 2021;Cao et al, 2009;Xu et al, 2021).…”
Section: Effect Of Extracts From Ssg On CCL 4 -Induced Liver Injury I...mentioning
confidence: 99%
“…From the perspective of TCM, various hepatic disorders appear the typical symptoms and key pathophysiological characteristics of "dampness-heat" syndrome, one of the most common TCM syndromes (Dai et al, 2013;Cao et al, 2009). Among the current animal models of liver injury, the carbon tetrachloride (CCl 4 )-induced hepatic damage has been demonstrated to properly represent the pathological features of "dampness-heat" syndrome in TCM, thus this model has been usually used in the experimental evaluation of potential therapeutic potentials of Chinese herbal medicines with heat-clearing, dampness-removing, and detoxifying properties (Xie et al, 2021;Cao et al, 2009;Xu et al, 2021). In the modern experimental research, the CCl 4 -induced liver injury model has been well-accepted to share similar pathomechanisms, such as inflammatory damage, oxidative stress, and hepatocyte apoptosis, with chemical liver injury in humans (Li et al, 2018;Ahmad et al, 2023).…”
Section: Introductionmentioning
confidence: 99%